Draft genome sequences of two biocontrol agents isolated from the maize phyllosphere: Bacillus subtilis strain EM-A7 and Bacillus velezensis strain EM-A8 - Fessia, Alumine Soledad (2024)
In the present study, the genomes of B. subtilis EM-A7 and B. velezensis EM-A8 were sequenced andannotated. The Illumina sequencing platform (NovaSeq PE150) was used to sequence the genomicDNA. There were 6 277 054 raw reads for EM-A7, with a Q20 of 97.52 % and 43.78 % GC, and 8030 262 raw reads for EM-A8, with a Q20 of 97.53 % and 46.21 % GC. Annotation was carriedout by the NCBI Prokaryotic Genome Annotation Pipeline (PGAP). The strains were classifiedtaxonomically on the basis of an average nucleotide identity analysis (ANI), as well as through adDDh analysis on the Genome-to-Genome Distance Calculator (GGDC v3.0). The pipeline predicted4062 protein-coding sequences (CDSs) and 73 RNA genes (62 tRNA and 6 rRNA) for EMA7,and 3797 protein-coding sequences (CDSs) and 80 RNA genes for EM-A8. These findingsenhance our understanding of the two strains’ potential as biocontrol agents to manage disease inmaize.